Something in the air - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Global estimates of gaseous emissions of NH3, NO and N2O from agricultural land International Fertilizer Industry Association & FAO, 2001. 116 pp ISBN 9251046891 US$12 Euro 12.15